2020
DOI: 10.1371/journal.pone.0236856
|View full text |Cite
|
Sign up to set email alerts
|

The macroecology of the COVID-19 pandemic in the Anthropocene

Abstract: Severe acute respiratory syndrome coronavirus 2, the virus that causes coronavirus disease 2019 (COVID-19), has expanded rapidly throughout the world. Thus, it is important to understand how global factors linked with the functioning of the Anthropocene are responsible for the COVID-19 outbreak. We tested hypotheses that the number of COVID-19 cases, number of deaths and growth rate of recorded infections: (1) are positively associated with population density as well as (2) proportion of the human population l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 75 publications
(103 reference statements)
2
25
0
Order By: Relevance
“…The high correlation between the longitude of the country centroid and DPMI and CFR emphasize a significant increase in CP and CFR from eastern to western regions in the world (Table 5; Figs. 4 and 5), as confirmed by Leung, Bulterys & Bulterys (2020) and Skórka et al (2020). Longitude could act as a proxy for variables such as lifestyle, social behavior, genetics, geographically isolated and remote populations, which may also be associated with CP and CFR.…”
Section: Discussionmentioning
confidence: 76%
“…The high correlation between the longitude of the country centroid and DPMI and CFR emphasize a significant increase in CP and CFR from eastern to western regions in the world (Table 5; Figs. 4 and 5), as confirmed by Leung, Bulterys & Bulterys (2020) and Skórka et al (2020). Longitude could act as a proxy for variables such as lifestyle, social behavior, genetics, geographically isolated and remote populations, which may also be associated with CP and CFR.…”
Section: Discussionmentioning
confidence: 76%
“…Some of co-temporary papers with similar design, confirmed importance of demographic factors. 9–18 Using slightly different set of predictors some studies showed an association of comorbidities more important than socioeconomic factors. 19 , 20 The question how effective particular non-pharmaceutical interventions are, is still unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…In USA, a study reported macrolevel association of COVID-19 burden and case-fatality with air pollution, gross domestic product (GDP) per capita and urbanization [ 34 ]. An international macroecological study reported association of COVID-19 burden and mortality with national GDP, urbanization, population density, number of tourists in a country and geographic longitude [ 35 ]. Influence of demographic and socioeconomic factors in the COVID-19 case-fatality rate globally was examined among 10.5 million cases in 209 countries.…”
Section: Discussionmentioning
confidence: 99%